Rare complication of ureteral double-J stenting after ureteroscopy: pelvic ectopic renal parenchymal perforation. Issue 1 (January 2022) - Huang, Chaoyou; Liu, Junbo; Mao, Juan; Yu, Luolian; Gong, Lifeng; Lai, Fei
Scarce data are available on pelvic ectopic renal parenchymal perforation. However, this complication might lead to serious consequences. Clinicians should pay attention to the early identification and treatment of this complication. We herein report the first case of pelvic ectopic renal parenchymal perforation caused by a double-J stent after ureteroscopy. Compared with previously reported cases of renal parenchymal perforation not involving an ectopic kidney, our case involved no renal capsule hematoma and no other serious complications. Our primary management strategy was to review relevant examinations and tests, perform close monitoring, and instruct the patient to stay in bed. The patient recovered smoothly after the ureteral stent was removed 1 month postoperatively.